Variability and Main Controlling Factors of Hydrocarbon Migration and Accumulation in the Lower Paleozoic Carbonate Rocks of the Tazhong Uplift, the Tarim Basin, Northwest China. (25th August 2021) - Fang, Qifei; Yao, Qingzhou; Qu, Yongqiang; Jiang, Youlu; Li, Huizhen; Dai, Dongdong; Fan, Shan; Zhu, Weiping; Yang, Lisha; Wang, Xiaoxue; Zhang, Min
Abstract : Hydrocarbon migration patterns and pathways were studied on the basis of three-dimensional seismic interpretation, drilling, geochemistry, production performance, and other data. Using these findings, the main factors controlling hydrocarbon migration and accumulation in the Lower Paleozoic carbonate rocks of the Tazhong Uplift were discussed. The spatiotemporal relationship between the hydrocarbon kitchens and pathway systems of the Tazhong Uplift and the spatial pattern of pathway systems were considered the main factors causing differences in hydrocarbon enrichment. Results also revealed that the Lower Paleozoic carbonates of the Tazhong Uplift have two hydrocarbon accumulation systems (inside and outside the source rocks). For the accumulation system within the source rocks, hydrocarbon migration and enrichment are vertically differentiated. Middle Cambrian gypsum salt rocks serve as the boundary, above which thrust and strike-slip faults mainly allow vertical transport of hydrocarbons. A multistage superposition pattern of strike-slip faults controls the differences in hydrocarbon enrichment on the periphery of the fault zone. Beneath the gypsum-salt rocks, hydrocarbon migration and enrichment is controlled by the topography of paleostructures and paleogeomorphology. For the hydrocarbon accumulation system outside the source rocks, hydrocarbon migration and enrichment are restricted by the layered pathway system, and the topography of the paleostructures and paleogeomorphology is the key factor controlling hydrocarbon enrichment. The Tazhong No. 1 Fault is the main vertical pathway system in the area underlain by no source rocks, and hydrocarbons are enriched at the periphery of the Middle-Lower Cambrian and No. 1 Fault Zone.